METABOLIC SYNDROME IN MADHUMEGAM (TYPE 2 DIABETES MELLITUS) PATIENTS REPORTING AT NATIONAL INSTITUTE OF SIDDHA – A CROSS SECTIONAL STUDY - Venkatesan Charumathi; Lakshmi Kantham T; Mohan S (International Journal of Ayurveda and Pharma Research, 2019)
Introduction: Madhumegam is a clinical condition characterised by frequent and excessive urination which ultimately leads to deterioration of seven body constituents and three humours. Its signs and symptoms may be correlated with Diabetes mellitus in modern science. Since, metabolic syndrome has become major cause of morbidity and mortality, identifying its cause and prevention has gained immense importance. Aim: This study aimed at determining the prevalence of metabolic syndrome in Madhumegam (Type 2 Diabetes mellitus) patients and to identify the most critical predictive risk factors of metabolic syndrome. Methods: This hospital based cross sectional study involved 100 type 2 diabetes mellitus patients and was conducted at Ayothidoss Pandithar Hospital, National Institute of Siddha. This study used questionnaire to obtain information on diabetic condition, anthropometric measurements and lipid profile. Metabolic syndrome was defined according to the International Diabetes Federation criteria. Results: The prevalence of metabolic syndrome was 53% in the study population. Elevated triglyceride was the commonest component (77.3%) followed by lowered HDL (51%). Female type 2 diabetic patients had a higher prevalence of metabolic syndrome (54.7%) than their male counterparts (45.3%). With respect to age, individual within the age group of 60-69 had highest prevalence of metabolic syndrome while age group of 30-39 has least prevalence of metabolic syndrome. Conclusion: Elevated triglyceride for men and lowered HDL for women were the strongest risk factors. Metabolic syndrome is a significant health problem and its preventive strategies should focus on early diagnoses and lifestyle modification.